THEORETICAL AND PRACTICAL EDUCATION OF PRIMARY SCHOOL STUDENTS ON THE BASIS OF INFORMATION AND PEDAGOGICAL TECHNOLOGIES (Academicia Globe: Inderscience Research, 2021)
The article examines the importance of using information and pedagogical technologies in primary school, as well as their application in theory and practice.